A Rare Congenital Cardiac Anomaly in Adulthood: Tetralogy of Fallot With Absent Pulmonary Valve Syndrome. (April 2014) - Saygi, Murat; Haydin, Sertac; Guzeltas, Alper; Odemis, Ender; Yeniterzi, Mehmet
In approximately 3% to 6% of the patients with tetralogy of Fallot (TOF), the pulmonary valve leaflets are absent or only a rudimentary ridge of tissue is present. Some infants with the severe form of this syndrome die early during the newborn period due to severe respiratory distress, feeding intolerance, or cardiovascular compromise. Survival to adulthood of this combination is extremely unusual. In this article, we presented a case who was diagnosed in adult age with TOF having absent pulmonary valve syndrome. The patient with these findings underwent surgery, and complete repair was performed. Clinical symptoms resolved after surgery.